DIGITAL TECHNOLOGIES AND MODERN PEDAGOGY: EVIDENCE FROM UZBEKISTAN - Baxtiyorova, Muminakhon; Qoshaqova , Gozalkhon (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
This study investigates the role of digital technologies in modern pedagogy by applying a mixed empirical approach that combines comparative analysis and econometric regression analysis. The research focuses on Uzbekistan and uses Japan as a benchmark country to illustrate differences in the stage and quality of educational digitalization. The comparative analysis examines cross-country differences in digital infrastructure, teacher ICT competence, and learning outcomes using data from international statistical sources. The econometric analysis employs a time-series regression model to estimate the relationship between digitalization indicators and educational performance in Uzbekistan. Diagnostic tests are conducted to assess model reliability, and short-term conditional predictions are used to illustrate potential trends. The findings indicate statistically significant associations between internet access, teacher ICT competence, and learning outcomes, while the availability of digital infrastructure alone shows mixed effects. These results provide empirical evidence on the differentiated role of digital technologies in education and contribute to the growing literature on digital pedagogy in developing education systems.